Congenital anterior urethral diverticulum in male child (Community Based Medical Journal, 2018)
Congenital anterior urethral diverticulum is an uncommon condition in males. In my series a 15 years old boy with congenital anterior urethral diverticulum was presented with urinary symptoms and ventral penile swelling. The diagnosis was made on retrograde urethrogram (RGU) and micturiting cystourethrogram (MCU). The patient had normal renal function. Open diverticulectomy and primary urethral reconstruction was carried out uneventfully.CBMJ 2018 January: Vol. 07 No. 01 P: 45-47